Rational design of nanocarriers based on gellan gum/retrograded starch exploiting polyelectrolyte complexation and ionic cross-linking processes: A potential technological platform for oral delivery of bevacizumab - Cardoso, Valéria Maria de Oliveira [UNESP] (2021)
The structural fragility of monoclonal antibodies (mAbs), such as bevacizumab (BVZ), is a critical parameter for oral administration and can limit the use of several technologies to produce oral nanocarriers for these biomolecules. Nanoparticles (NPs) based on gellan gum (GG) and retrograded starch (RS) were rationally designed through polyelectrolyte complexation, and ionic cross-linking was exploited as an additional technological strategy to modulate the properties of nanocarriers. According to static light scattering analysis, the molecular weights of GG and RS were approximately 158 kDa and 1803 kDa, respectively. The influence of pH on the zeta potential (ZP) of polymers allowed the selection of pH 6.2 as the most suitable pH for the complexation of these polyelectrolytes. Non-cross-linked NPs were prepared at different polymer:drug ratios and the effects of formulation variables (polyelectrolyte ratio, drug and cross-linker concentrations, and polymer:drug ratio) on the formation and properties (size, ZP, and PDI) of cross-linked NPs were evaluated using a 33 full-factorial design. The average size of non-cross-linked and cross-linked NPs ranged from 260.1 - 299.6 nm to 265.7–629.9 nm, respectively. NPs-negative ZP (>- 20 mV) and high association efficiency (AE%) (>56.16%) were achieved. Cross-linking significantly increased the BVZ AE% (85%–100%). Analyses by attenuated total reﬂectance-Fourier transform infrared, fluorescence, circular dichroism, and differential scanning microcalorimetry techniques demonstrated that polyelectrolyte complexation and ionic cross-linking did not denature the secondary and tertiary structures of BVZ. The results revealed the suitability of the technological approaches used to produce BVZ-loaded nanocarriers with tailored properties, representing a potential platform for the oral delivery of BVZ.